Development and optimization of a novel grain flow sensor based on PVDF piezoelectric film - He, Wang; Jingtao, Hu; Lei, Gao; Yanfeng, Jia (International Journal of Agricultural and Biological Engineering, 2016)
A novel grain flow sensor consists of an impact plate and a PVDF (Polyvinylidene Fluoride) piezoelectric film was developed in this research. The kinetic model of the grain flow sensor was built to analyze the steady and transient vibration disturbances which had a significant influence on performance of the sensor, and the results showed that damping ratio of the sensor was the key factor to improve accuracy of the sensor. To maximize damping ratio of the sensor, the thickness of the impact plate and damping material were optimized according to a loss factor model of the free damping structure. The optimized results indicated the most appropriate thickness ratio of damping material and the impact plate was 6. A test rig equipped with the novel grain flow sensor and weight sensors which could simulate field situations was built to investigate the performance of the sensor, on which test experiments under different feed flows were conducted. The results showed that the maximum error of the sensor was 3.02% and the mean error was 2.15%, which revealed that the novel grain flow sensor could be used to measure grain flow. Comparing with conventional grain flow sensors, the novel grain flow sensor has the features of high accuracy, simple structure and flexible signal processing methods.Keywords: grain flow sensor, vibrations, free damping structure, test rigDOI: 10.3965/j.ijabe.20160904.1887Citation: Wang H, Hu J T, Gao L, Jia Y F. Development and optimization of a novel grain flow sensor based on PVDF piezoelectric film. Int J Agric & Biol Eng, 2016; 9(4): 141－150.